Relation between Heat Stress and Some Hormones in Alloxan Induced Diabetic Rats - Ihsan Raisan Ibrahim ,; Ahmed Jassim AL-naely , (University of Thi-Qar Journal of Science, 2020)
The current study carried out to evaluate the levels of corticosterone, epinephrine, insulin and thyroxine accompanied induced diabetes mellitus in rats. Therefore, ninty six rats were divided into two main groups: control group which exposed to normal temperature (21±2) °C and second group which exposed to high temperature (40±2)°C each main group subdivided into three subgroups exposed to temperature for one, two and four hours respectively, also each subgroup composed of healthy rats and diabetic rats equally. At the end of experiment blood samples were collected for determination of corticosterone epinephrine, insulin and thyroxine.Results revealed significant increase in corticosterone and epinephrine and insulin in heat stressed group compared with control group while there was significant decrease in thyroxine in healthy and diabetic rats in heat stressed group compared with control group.Results showed significant increase in corticosterone in diabetic rats compared with healthy rats in both groups ,while the significant increase in epinephrine and insulin in diabetic rats was only in heat stressed group.Results reported significant decrease in corticosterone and thyroxine according to the increase in heat exposure duration,while epinephrine and insulin increased according to the duration. These findings indicated that heat stress may be increase harmful effects in alloxan induced diabetic rats.